Antimicrobial prophylactic practice in surgical patients - al Harbi, M (East African medical journal, 1998)
To evaluate the prescribing patterns of surgeons for pre-operative antimicrobial prophylaxis. A retrospective study based on data obtained from case records of surgical patients admitted into the Department of Surgery. Department of Surgery, Royal Commission Medical Center, Madinat Yambu Al-Sinayah. The study population comprised of 888 surgical patients who received antibiotic therapy either for prophylaxis or treatment during the period 1st November 1992 and 28th February 1995. A total of 888 surgical patients received antibiotics during the study period, 191 (21.5%) for prophylaxis while 697 (78.5%) were given antibiotics for therapy before and after surgery. Ceftriaxone was the most commonly used antibiotic for prophylaxis, followed by augmentin and cefotaxime, and these were frequently given in multiple doses, extending beyond 24 hours. There was unwarranted and over use of prophylactic agents in at least 70% of the patients, with increased costs to the Hospital. Effective prophylaxis can be accomplished with a single dose of a cephalosporin, such as ceftriaxone, cefuroxime or cefazolin, for the common surgical procedures. It is recommended that better compliance with principles of surgical antimicrobial prophylaxis be implemented Prophylactic antibiotic audit measures should be carried out by the control committee. The development of guidelines and standing orders for antimicrobial prophylaxis should help to improve compliance.